Use and Regulation of the Radio Spectrum: Report on a Conference - William K. Jones (Washington University Law Quarterly, 1968)
This Article begins by briefly outlining the present mode of determining access to the radio spectrum. The second section reviews the attack upon this method by some of the academic economists, and states their proposal for establishing a market in transferable spectrum rights. The next two sections consider the problems presented by such a market system and a number of alternative proposals for revision of spectrum management practices. The impact on spectrum use of a number of recent technological developments is briefly reviewed in Section V. A few concluding observations are appended in Section VI.
Keywords: Spectrum usage; Radio spectrum